Social change in an urban neighbourhood in Klang a case study - Jayanath Appudurai; Lian, Kwen Fee 1950- (Strategic Information and Research Development Centre, 2015)
The authors, a retired Malaysian diplomat and a senior sociologist undertook this research, using both quantitative and qualitative methodologies, to determine how an urban community n the outskirts of the capital city had adapted to change since the 1980s and 1990s. The community they studied was comprised mainly of Indians from the estates and Malays from villages. Both groups were trying to cope with the transformation into being urban dwellers in a mixed community having previously been used to more homogeneous living in their places of origin. 70 pages with references and an appendix.